Evaluation of consumer protection council with special reference to erode dirstrict - N A, Krishnamurthi; K M, Suresh (Journal of Management and Science, 2014)
India is a vast country where a majority of consumers are poor, helpless and disorganized. Further, the Market in India is generally a sellers Market and it is very easy to cheat the innocent consumers. It is now realized that a common consumer is neither knowledgeable nor well-informed. He/she needs support and protection from the unscrupulous seller. A common consumer is not in a position to approach a civil court.Quick, cheap and speedy justice to his/her complaints is required. The biggest help in this direction has come from the Government. The Central Government enacted a Law known as ―The Consumer protection Act, 1986‖.Consumer protection council is a social movement which seeks to protect and argument the rights of the consumer in relation to the producers.